TERRITORIAL AND ADMINISTRATIVE REFORMS IN THE NAMANGANUYEZD OF THE RUSSIAN EMPIRE IN THE SECOND HALF OF THE 19TH CENTURY AND THEIR CONSEQUENCES (Universal International Scientific Journal, 2026)
This article describes the transformation of Turkestan into a governor-generalship after the conquest of the Russian Empire and the numerous administrative territorial divisions that occurred. It also describes the geographical location of Namangan uyezd and its division into volosts, rural and nomadic communities. In addition, information is provided about the territorial changes that occurred in the territory of Namangan uyezd
Keywords: Turkestan; Uyezd; Governor-General